Energy boosting and scaling of self-guided hybrid laser-plasma wakefield acceleration in a single uniform plasma - Xinyuan Chang; Ming Zeng; Jia Wang; Dazhang Li (New Journal of Physics)
In laser-driven plasma wakefield acceleration (LWFA), laser pump depletion and electron dephasing are the major constraints of the electron energy gain. Hybrid laser-PWFA, which uses the laser-accelerated electron beam to drive a beam-driven plasma wakefield in separated stages, has been proposed to increase the beam brightness. However, the overall electron energy gain in hybrid acceleration is even lower than single-stage laser acceleration. In this paper, we report the observation of the energy boosting effect of the hybrid acceleration in single uniform plasmas through a series of particle-in-cell simulations. The self-injected electron beam from the laser-driven wakefield automatically moves forward to drive the beam-driven wakefield after laser depletion. The electrons at the beam tail are then accelerated by the beam-driven plasma wakefield, and the energy gain is at least doubled compared to previous single-stage experiments with the same laser energy. We also propose the scaling of the electron energy gain and the acceleration distance with the laser energy. For example, with a 9.1 J energy laser pulse and a 3.5 cm long plasma of $1.6 × 10^{18}\ cm^{-3}$ density, one can produce a quasi-monoenergetic electron beam at 3.5 GeV energy with 23 pC charge.